A Case of Chronic Abdominal Neuropathic Pain and Burning after Female Genital Cutting - Vicky Hadid; Michael Haim Dahan (Case Reports in Obstetrics and Gynecology)
Introduction. Female genital cutting is prevalent in the Middle Eastern and African countries. This ritual entails not only immediate complications such as infection, pain, and haemorrhage, but also chronic ones including dysmenorrhea and dyspareunia. However, there is limited data on neuropathic pain secondary to female genital mutilation when searching the literature. Case. This case discusses a 38-year-old female with a history of infibulation who presented with a chronic burning abdominal and anterior vulvar pain including the related investigations and treatment. Discussion. This case brings to light the additional delayed complication of this ritual: sensory neuropathy. Our goal is to educate health professionals to be aware of these complications and to appropriately investigate and treat them in order to find a solution to relieve the patients’ symptoms.